2016
DOI: 10.1155/2016/6969726
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Potency Analyses of Donor‐Matched Chondrocytes and Mesenchymal Stem Cells Derived from Bone Marrow, Infrapatellar Fat Pad, and Subcutaneous Fat

Abstract: Autologous chondrocyte implantation (ACI) is a cell-based therapy that has been used clinically for over 20 years to treat cartilage injuries more efficiently in order to negate or delay the need for joint replacement surgery. In this time, very little has changed in the ACI procedure, but now many centres are considering or using alternative cell sources for cartilage repair, in particular mesenchymal stem cells (MSCs). In this study, we have tested the chondrogenic potential of donor-matched MSCs derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 41 publications
4
52
0
1
Order By: Relevance
“…MSCs represent a defined population of multipotent progenitor cells residing in the perivascular niche of nearly all human tissues, although different views exist (Crisan et al, 2008;Guimaraes-Camboa et al, 2017). MSC differentiation capacity and immunomodulatory properties are demonstrated in vitro, irrespective of tissue sources (Ghannam et al, 2010). However, in vitro studies show that MSCs from different origins differ in their lineage-specific differentiation capacity and their functional potential (Garcia et al, 2016;Islam et al, 2016;Subramanian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs represent a defined population of multipotent progenitor cells residing in the perivascular niche of nearly all human tissues, although different views exist (Crisan et al, 2008;Guimaraes-Camboa et al, 2017). MSC differentiation capacity and immunomodulatory properties are demonstrated in vitro, irrespective of tissue sources (Ghannam et al, 2010). However, in vitro studies show that MSCs from different origins differ in their lineage-specific differentiation capacity and their functional potential (Garcia et al, 2016;Islam et al, 2016;Subramanian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…MSC differentiation capacity and immunomodulatory properties are demonstrated in vitro, irrespective of tissue sources (Ghannam et al, 2010). However, in vitro studies show that MSCs from different origins differ in their lineage-specific differentiation capacity and their functional potential (Garcia et al, 2016;Islam et al, 2016;Subramanian et al, 2015). In addition, a systematic review of intra-articular injection of bone marrow MSCs in humans has concluded that articular stem cell therapies are safe (Peeters et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we aim to gain a better understanding of the healing response in the joint and how this differs between individuals by studying biopsy tissue from chondrocyte harvest sites, where the initial 'injury' was created under controlled conditions. Finally, we are assessing the characteristics of both cell types for predictors of potency; such analyses will include cell growth kinetics and morphological analyses as well as RNA sequencing and immunoprofiling by flow cytometry, using similar profile analyses to those we have previously published [45]. The actual markers analyzed for both techniques are constantly being updated as the study progresses to keep up to date with current literature and available technologies, future science group Efficacy & safety of autologous cell therapies for knee cartilage defects (ASCOT) Clinical Trial Protocol but regardless of this, all cells are assessed for their adherence to the International Society for Cellular Therapy profile for MSCs (i.e., positive for CD73, CD90 and CD105 and negative for CD14, CD34, CD45, CD19 and HLA-DR).…”
Section: Cell Characterization and Biomarker Studiesmentioning
confidence: 99%
“…On the perspective of functional performance of cells, the risk of chondrocyte de‐differentiation, or lack of potency of the autologous chondrocytes along the need for double surgery and prolonged surgical pre‐planning, has inspired the study of alternative cell sources, including mesenchymal stromal/stem cells (MSCs) in general, and adipose‐derived stromal/stem cells (ASCs) in particular . As compared with other MSC sources, adipose tissue can be harvested with reduced morbidity at the donor site and yields of ASC are considerably high .…”
Section: Introductionmentioning
confidence: 99%